Optical coherence tomography versus angiography to guide percutaneous intervention: a real-world single center propensity-matched analysis. (4th February 2022) - Dadarwal, A; Roy, S; Sharma, A K; Sharma, K K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Optical coherence tomography (OCT) with its superior resolution has several benefits over coronary angiography (CA) to guide percutaneous coronary intervention (PCI). Despite the benefits of OCT in comparison with angiography, it is not widely used in developing countries like India data is limited in India specifically in all comer population to meet unmet need. Objective: Here we aim to determine the clinical efficacy and safety outcomes of OCT versus CA alone in guiding PCI in all-comer patients. Methods: This was a retrospective study which included 434 all comer patients which were propensity matched. These patients underwent PCI at our center between December 2018 and June 2020. The primary endpoint was MACE, a composite of cardiovascular death, repeat revascularization, stent thrombosis, recurrent ischemia and target vessel myocardial infarction (TV-MI) at 6 months. Secondary endpoint was target lesion failure (TLF), composite of stent thrombosis and in-stent restenosis. Safety endpoints were post-PCI s. creatinine and hospital stay and other outcome includes post PCI rise in CK-MB. Results: A total of 217 patients were included in each group: the OCT group and conventional angiography guided PCI (angio group) after propensity matching. Compared to angio group, patients presenting with unstable angina, NSTEMI were significantly higher in the OCT group (55.7% vs 43.3%, p = 0.0095; 17.5% vs 10%, p = 0.02, respectively) while patients with STEMI were significantly low in the OCT (23.5% vs 41.5%, p = 0.00005). Number of balloons, maximum balloon size and left main interventions and contrast volume were more in OCT group than angio group (4.21 ± 1.67 vs 3.86 ± 1.76, P= 0.0034; 3.77 ± 0.63 mm vs 3.51 ± 0.52 mm, P < 0.0001; 24.52% vs 13.36 %, P = 0.003 and 202.53 ± 73.15 ml vs 161.91 ± 69.23 ml, P< 0.0001 respectively). The incidence of MACE at 6 months was numerically lower in the OCT group vs angio group but the difference was not statistically significant (15 [6.9%] vs 21 [9.7%]; p = 0.2964). No cases of TV-MI, TLF (stent thrombosis or in-stent restenosis) is observed in both the groups. Post procedure rise in CKMB was more in Angio group in comparison to OCT group (6.16 ± 31.28 ng/ml vs 39.5 ± 108.71 ng/ml, p < 0.001). Optimal stent expansion (>80%) was seen in 71.5% patients in post OCT-guided PCI. In OCT guided PCI group, OCT identified stent underexpansion in 28.5%, stent malapposition in 3.7%, stent edge dissection in 4.1%, and tissue prolapse in 10% of the patients. Conclusion: In this large retrospective study, OCT guided PCI is feasible and OCT-guided PCI has tendency to improve clinical outcomes at six months follow up compared to conventional angiography guided PCI in all comer patients.